Vacuum-packaged versus conventionally packaged ground beef: the influence of packaging on consumer acceptance and flavor characteristics - Lynch, N.M.; Caul, J.F.; Kropf, Donald H.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Vacuum-packaged ground beef was compared to a conventionally packaged (polyvinyl chloride) product to determine consumer flavor and aroma preferences. In addition, flavor characteristics were described and quantified by a trained panel. Consumer panels slightly preferred the cooked beef flavor of the conventionally packaged product and the raw aroma of the vacuum-packaged product. Conventionally packaged samples displayed for 3 days and then cooked were slightly less beefy, less fresh, more stale, slightly less bloody/serumy, slightly less sour, and had less of a metallic mouth feel than vacuum-packaged samples stored 12 days and cooked. Throughout display, flavor of the vacuum-packaged samples was more consistent than that of the conventionally packaged samples. Based on flavor and aroma characteristics, vacuum-packaged ground beef should compete favorably in the marketplace.
Keywords: Beef; Ground beef; Packaging; Flavor; Consumer